Raiders! - "Benton, Lynne" (Heinemann Educational Publishers: Jordan Hill, 1998)
Literacy World is evolving with the renewed Framework to provide all the support you need to deliver Shared Reading and Writing, Guided Reading, ICT and Speaking and Listening at Key Stage 2/P4-7. A wealth of quality resources, exceptional teacher support and complete differentiation make Literacy World your only choice for fiction and non-fiction at Key Stage 2/P4-7.
Keywords: Children's fiction